NASIONALISME, DEMOKRATISASI, DAN SENTIMEN PRIMORDIAL DI INDONESIA : PROBLEMATIKA IDENTITAS KEAGAMAAN VERSUS KEINDONESIAAN (KASUS ORMAS PENDUKUNG KHILAFAH ISLAMIYAH) - Syafuan Rozi (Pusat Penelitian Politik, 2010)
AbstractThis article is a desk review or literature study about the raising ofreligious sentiment ofpolitical identity withvarious expressions related to some Islamic movements such as HTI Hizbut Tahrir Indonesia Tarbiyah movementand MM Majelis Mujahidin Indonesia in Indonesia s post Soeharto era This kind of movements can be seenas a phenomenon ofpolitical movement and religious awareness as critical mass toward Indonesian nation stateor secular nationalism The contestation of the meaning of keindonesiaan such as spirit of tolerance equalityand appreciation ofpluralism anti andpro secular liberalism reducingpoverty and increasing wealth and goodmanners in theface ofsearchingfor model or alternative ofnewform ofthe state which promoted by the KhilafahIslamiyah movement and supporters This research elaborated issues such as howfar religious values and khilafahprinciples implemented by various Islamic movements towards Khilafah Islamiyah states and howfar it will makeimpact toward Indonesian nation state atpresent and in the future The general questions of this research namelywhat are the basic and core values ofpolitical thinking ofthis groups in order to convince the people that KhilafahIslamiyah is an alternative ofthe future state and how they implement their principles What kind ofstrategic andstep they take in order to prove that their vision will become reality or not Finally how big their ideas and theirmovement may counter the keindonesiaan principle as best practice or alternative in political development